2005
DOI: 10.1002/eji.200425958
|View full text |Cite
|
Sign up to set email alerts
|

Limited correlation between human thymus and blood NKT cell content revealed by an ontogeny study of paired tissue samples

Abstract: NKT cells are a CD1d-restricted T cell subset with strong immunoregulatory properties. Human NKT deficiencies are associated with autoimmune diseases such as type 1 diabetes and several types of cancer, yet there is little understanding of how the human NKT cell pool develops or is maintained. In this study, we present the first detailed analysis of human NKT cells from donor-matched postnatal thymus and blood samples. In mice, NKT cells are a thymus-dependent population that migrates to the periphery at an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
111
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 36 publications
(72 reference statements)
15
111
0
2
Order By: Relevance
“…The functional potential of subsets of human NKT cells has been well studied, and they have been reported to play vital roles in autoimmune diseases, such as type 1 diabetes and several types of cancer. [57][58][59] Our results provide an explanation for the emergence of CD8 1 iNKT cells in ThPok-deficient mice and suggest an indirect correlation between Runx3 and the function of iNKT cells using DKO mice. However, the precise mechanisms by which Runx3 and ThPok influence the subsets and functions of iNKT cells in mice remain to be elucidated.…”
Section: Discussionmentioning
confidence: 55%
“…The functional potential of subsets of human NKT cells has been well studied, and they have been reported to play vital roles in autoimmune diseases, such as type 1 diabetes and several types of cancer. [57][58][59] Our results provide an explanation for the emergence of CD8 1 iNKT cells in ThPok-deficient mice and suggest an indirect correlation between Runx3 and the function of iNKT cells using DKO mice. However, the precise mechanisms by which Runx3 and ThPok influence the subsets and functions of iNKT cells in mice remain to be elucidated.…”
Section: Discussionmentioning
confidence: 55%
“…1,33,46 The three earlier studies linking MDS to NKT cell deficiency used less stringent approaches, including a definition of NKT cells as Va24 þ Vb11 þ CD4ÀCD8À 11 (excluding legitimate CD4 þ NKT cells, which comprised B40% of NKT cells in our study), or Va24 þ CD161 þ cells 12 (excluding legitimate CD161À NKT cells, while including Va24 þ Vb11ÀCD161 þ non-NKT cells). The third study identified NKT cells as Va24 þ Vb11 þ , 10 which usually provides a reasonably accurate approximation of NKT cell frequency, 46,47 despite not necessarily identifying all NKT cells. 48 Therefore, we suggest a more likely explanation for the discrepancy is that the earlier study pooled results from treated (not with lenalidomide) and untreated patients, whereas we separately assessed the NKT cell frequency of patients before and after treatment with lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological function of NKT cells is still somewhat paradoxical, as they have been implicated as regulatory T cells controlling autoimmunity, immunity to pathogens and tumors, as well as effectors of immune-mediated damage [34][35][36]. They are present in low numbers in neonatal human thymus and blood as well as adult human blood [37]. Other populations under the umbrella term 'T reg ' have recently been described in human fetal thymus, spleen and MLN [38].…”
Section: Discussionmentioning
confidence: 99%